A healthy indulgence? Wine consumers and the health benefits of wine - Lindsey M. Higgins; Erica Llanos (Wine Economics and Policy, 2015)
Heart disease is the leading cause of death in the US. Moderate red wine consumption has been linked to a reduction in the risk of death by heart disease and heart attack by 30-50%. With about 600,000 people dying from heart disease in the US each year, red wine has become increasingly popular among health conscious consumers. Wine is often touted for its potential health benefits, but to what extent is "health" a factor when consumers make their consumption decisions for alcoholic beverages? This study aims to further understand how consumers make their beverage choices and to understand the role wine health benefit knowledge plays in the willingness of consumers to purchase wine. The results suggest that consumers value the relationship between food/beverage intake and their health status. Consumers with few health issues were the ones more likely to indicate that they consume wine for health reasons, suggesting a potential market among consumers with known health issues. In addition, consumers who attributed the most health benefits to wine were the ones most likely to drink more wine and pay more for wine if it were health enhanced.
Keywords: 330; Consumers; Functional foods; Health; Marketing; Wine